1999
DOI: 10.1021/la990325x
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Dehalogenation of Trichloroethylene with Zero-Valent Iron:  Surface Profiling Microscopy and Rate Enhancement Studies

Abstract: Mechanistic aspects of the reductive dehalogenation of trichloroethylene using zerovalent iron are studied with three different surface characterization techniques. These include scanning electron microscopy, surface profilometry, and atomic force microscopy. It was found that the pretreatment of an iron surface by chloride ions causes enhancement in the initial degradation rates. This enhancement was attributed to the increased roughness of the iron surface due to crevice corrosion obtained by pretreatment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
64
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 24 publications
3
64
0
Order By: Relevance
“…, respectively, a 22% and 50% increase compared with that when Cl À was absent. On the other hand, Gotpagar et al (1999) reported that pretreatment of the iron surface by chloride ions was able to enhance the initial degradation rate of trichloroethylene with ZVI. Johnson et al (1998) observed that addition of chloride ions increased the rate of CCl 4 dechlorination with ZVI by as much as four times.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…, respectively, a 22% and 50% increase compared with that when Cl À was absent. On the other hand, Gotpagar et al (1999) reported that pretreatment of the iron surface by chloride ions was able to enhance the initial degradation rate of trichloroethylene with ZVI. Johnson et al (1998) observed that addition of chloride ions increased the rate of CCl 4 dechlorination with ZVI by as much as four times.…”
mentioning
confidence: 99%
“…First, the addition of chloride ions can enforce the breakdown of the thin film of iron (hydr)oxides on ZVI surface. Hard Lewis base ions (such as Cl À , Br À , and I À ) were reported to be especially aggressive toward the passivating oxide layers to form strong complexes with iron centers (Gotpagar et al, 1999;Johnson et al, 1998). As the oxide layers are broken down by these diffusing anions, more ZVI surface becomes available for perchlorate reduction, resulting in improved perchlorate degradation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first step in the reaction of Fe 0 and a TCE solution is TCE sorption onto the iron surface [11]. From the XRD analysis of the surface coatings, the iron surfaces are covered by iron oxides, Fe 3 O 4 (magnetite)/Fe 2 O 3 (maghemite).…”
Section: Discussionmentioning
confidence: 99%
“…Later studies indicate that the introduction of a second, catalytic metal, results in increasing the half-life of Fe 0 [14][15][16][17]. Bimetallic combination of iron with metals such as nickel (Ni), copper (Cu), zinc (Zn), palladium (Pd) and silver (Ag) can degrade halogenated hydrocarbons in water much better than ZVI nanoparticles as electron transfer from Fe 0 is catalysed by the secondary metal and the rate of electron transfer is maintained constant [15,16,18,19].…”
Section: Introductionmentioning
confidence: 99%